Analysis of Student Response to the Use of Smart Six Application in Mathematics Assessment - Aryo Adhi Wibisono; Alfiatun; Irma Ainur Hasanah; Lutpi Abdul Latip; Neneng Aminah; Dede Endang Mascita (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The advancement of digital technology has significantly transformed education, including the adoption of online-based assessments. This study investigates students' responses to the use of the Smart Six application for end-of-semester assessments in Mathematics at SMAN 6 Cirebon. Smart Six is a school management application offering features such as data management, attendance tracking, scheduling, and online assessments. However, the abstract and visually intensive nature of Mathematics, which often requires manual calculations and visual aids, raises concerns about the application's effectiveness for such assessments. Using a descriptive research method, the study involved 76 grade 12 MIPA students as participants. Data were gathered through a questionnaire comprising 14 statements focused on two key indicators: students' acceptance of the ease of using Smart Six and the application's performance in supporting assessment requirements. The findings highlight that while Smart Six positively impacts the ease of conducting tests, challenges persist in solving Mathematics problems through the application, with over half of the students reporting difficulties. This study contributes to understanding the potential and limitations of integrating online-based technology into the assessment process, particularly for complex subjects like Mathematics.